Airway remodelling with spatial correlations: Implications for asthma pathogenesis - Pascoe, Christopher D.; Green, Francis H.Y.; Elliot, John G.; James, Alan L.; Noble, Peter B.; Donovan, Graham M. (Respiratory physiology & neurobiology, 2020)
•Airway remodelling is a cardinal feature of asthma.•Airway remodelling may exhibit spatial correlations in its structure.•Such correlations are plausibly formed by a mechanotransduction pathway driven by airway constriction. Airway remodelling is a cardinal feature of asthma in which airways undergo structural changes - in particular, increased airway smooth muscle mass and total airway wall area. Remodelling has long been thought to have functional consequences in asthma due to geometric effects that can increase airway narrowing and luminal occlusion. Prior studies have examined the distribution of remodelling between and within patients, but none have yet considered the possibility for spatial correlations in airway remodelling. That is, is remodelling clustered locally, or interrelated along proximal and distal locations of the bronchial tree? In view of recent interest regarding airway remodelling produced by mechanical stimuli, we developed a mathematical model to examine whether spatial correlations in airway remodelling could arise due to cycles of bronchoconstriction and mechanotransduction. Further, we compared modelling predictions to the spatial distribution of airway remodelling in lungs from subjects with and without asthma. Results indicate that spatial correlations in airway remodelling do exist in vivo, and cycles of bronchoconstriction and mechanotransduction are one plausible mechanism for their origin. These findings offer insights into the evolution of airway remodelling in asthma, which may inform strategies for treatment and prevention.